Development of Mobile and Spatial Based Smart Community Applications to Improve the Community Economy - Ionia Veritawati; Adi Wahyu Pribadi; Amir Murtako; Bambang Riono (Green Publisher Indonesia, 2025)
The economy in Depok Community is a problem, where the community needs support from the surrounding community and stakeholders in developing its economy. In planning, Depok is planned to become a smart city. Smart community is part of a smart city with a concept that includes technology-people-innovation in developing society. For this reason, this research developed the Smart Community concept which uses mobile and spatial-based technology to help improve the economy of its citizens, including MSME business actors in the sub-district area, especially in Cilodong Sub-district in this case study. The application development method uses the water fall methodology and an object-oriented approach. The results obtained, the application developed can be used by citizens to share information and communicate to help the citizens' economy, one of which is online marketing, and assisting stakeholders in monitoring and providing support in economic matters.